PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TERHADAP KETERAMPILAN BERARGUMENTASI SISWA KELAS V SEKOLAH DASAR PADA MATA PELAJARAN IPS - Solikhah, Oktaviamatus; Rezania, Vanda (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The cooperative learning model of the Student Team Achievement Division (STAD) type is an interactive learning model. The learning process requires something meaningful, can be applied to solve existing problems through arguing in argumentation skills. Based on the problems encountered, there are many students who have difficulty expressing opinions in class. The emergence of these problems because of the lack of confidence of students when speaking in front of the class. This problem occurs due to the lack of maximum social studies teaching carried out by the teacher. Therefore this study aims to determine the effect of the STAD type cooperative learning model on the argumentation skills of fifth grade elementary school students in social studies subjects at SDN Berbek Waru with the hope that argumentation skills will function to make social studies learning more meaningful through argumentation activities. This study uses a quantitative experimental approach, with a quasi-experimental design. The population and sample used 5th grade students with a total of 24 people. Data collection techniques using observation sheets and documentation. The data analysis technique used the normality test and the Paired Sample T-Test. Based on the results of the study, it was obtained that the average pretest of argumentation skills showed a result of 14%, while the posttest of 13% the null hypothesis (Ho) was rejected while the alternative hypothesis (Ha) was accepted, which means that there is an effect of applying the STAD type cooperative learning model to students' argumentation skills.